2002
DOI: 10.1182/blood-2002-01-0073
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of SOCS3 confers resistance to IFN-α in chronic myelogenous leukemia cells

Abstract: IntroductionInterferon ␣ (IFN-␣) is an important therapeutic cytokine that exerts antitumor activity in a variety of tumor cells. 1,2 Chronic myelogenous leukemia (CML) is one of the hematologic malignancies that responds well to IFN-␣ therapy. [3][4][5] However, the effect of the therapy is limited because of the development of resistance to IFN-␣, which has often been observed in patients with CML in the late chronic phase, accelerated phase, or blastic phase. 5 Although efforts to understand the molecular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 37 publications
6
60
1
1
Order By: Relevance
“…Loss of SOCS3 function results in elevated STAT5 activation leading to higher metastasis in colorectal carcinoma patients [89]. SOCS3 expression is elevated in chronic myeloid leukemia (CML) and confers resistance to interferon α (IFNα) treatment [90] indicating that expression of SOCS3 is associated with disease progression.…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 99%
“…Loss of SOCS3 function results in elevated STAT5 activation leading to higher metastasis in colorectal carcinoma patients [89]. SOCS3 expression is elevated in chronic myeloid leukemia (CML) and confers resistance to interferon α (IFNα) treatment [90] indicating that expression of SOCS3 is associated with disease progression.…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 99%
“…In support, three IFN-insensitive WM 1158R, WM 9 and 1205 Lu melanoma lines had high basal expression of SOCS 3 compared to sensitive cells. Furthermore, breast cancer (Evans et al, 2007) and leukaemia cells (Sakai et al, 2002) showed elevated constitutive expression of SOCS 1 and SOCS 3 and the resistance to proinflammatory cytokines including IFN-g. Perhaps IFN sensitivity of a SOCS 3 promoter is reduced due to aberrant expression of an activatory transcription factor(s). In this context, aberrant activation of tissue-specific promoters has been observed in cancers (Kovarik et al, 1993).…”
Section: Expression Profiles Of Socss In Melanoma Cellsmentioning
confidence: 99%
“…These studies indicated that aberrant silencing could be a cause for constitutive activation of JAK/STAT pathway in cancer cells. However, other studies also indicated that malignant cells compared to their normal counterparts express SOCS genes constitutively (Sakai et al, 2002;Li et al, 2004;Evans et al, 2007) and forced expression of SOCS transgene often conferred resistance to IFN. Constitutive expression can potentially hamper immunotherapy by inactivating cytokine signals.…”
mentioning
confidence: 99%
“…Persistent expression of SOCS1 and/or SOCS3 is observed in several haematological malignancies. Such as cutaneous T cell lymphoma, chronic myeloid leukemia, ALK+ anaplastic large cell lymphoma and some acute leukemia (Schuringa et al, 2000;Brender et al, 2001;Sakai et al, 2002;Cho-Vega et al, 2004;Roman-Gomaz et al, 2004). Also, in patients with colorectal cancer, papillary thyroid cancer, glioblastoma primary tissues, breast cancer and hepatocellular carcinoma tumors protein expression of SOCS1 and SOCS3 (Sasi et al, 2010;Wu et al, 2011;Ayyildiz et al, 2014;Kobawala et al, 2017).…”
Section: Discussionmentioning
confidence: 99%